Lectures in synergetics - Sugakov, V. I
Includes bibliographical references (pages 201-204) and index.; The world that surrounds us is a complex system of interacting objects. The versatility of the links and interactions brings about the infinite multiplicity of natural phenomena. â€œSynergeticsâ€ studies nonlinear nonequilibrium processes and self-organization phenomena, allowing for description, systematization and generalization of the phenomena that are described by the different branches of natural science: physics, chemistry, biology, as well as sociology and economics. This book introduces the reader to the exciting world of the nonlinear phenomena that are studied in synergetics. The book comprises treatises on mathematical methods for the study of nonequilibrium processes and presents versatile phenomena studied in synergetics: multistability, self-oscillation, spatial stratification, autowaves, kinetic phase transitions and chaos. Examples of self-organization in physics, chemistry, biology covered in this volume include laser generation, optical bistability, self-oscillations in semiconductors and chemical reactions, spatial stratification in hydrodynamics and in crystals, auto-waves in semiconductors and nerve fibers and many other phenomena. The majority of the phenomena considered occur in physics but the book is also useful for chemists and biologists